Thyroid screening in neonates: Indian perspective - Dr. Rabindran; Dr D Sharad Gedam (Pediatric Review: International Journal of Pediatric Research, 2015)
Hypothyroidism is most common preventable cause of Mental retardation. Most of developed countries have been adopted neonatal thyroid screening programme three decades back. In India still congenital hypothyroism is important preventable cause of mental retardation. Universal Neonatal thyroid screening looks a distant dream in Indian scenario.